2014
DOI: 10.2298/gensr1403815b
|View full text |Cite
|
Sign up to set email alerts
|

Sequential path analysis for determining interrelationships between yield and related traits in tobacco (Nicotiana tabacum L.) under normal and abiotic stress conditions

Abstract: In the present work the relationships between yield and its related traits were investigated in tobacco genotypes under normal and abiotic stress conditions (Orobanche aegyptiaca weed) at Urmia Tobacco Research Centre, Iran, during 2006-2009 cropping seasons. The experimental design was a randomized complete block design (RCBD) with three replications in each condition every year. Analysis of variance revealed extent genetic variability among the genotypes for most of the traits studied. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…G1, G3, G4, G9, G13, G16, G18, G21, G22 and G24) could be used for improving fresh and dry leaf yield traits in tobacco breeding program. The leaf properties including leaf length, leaf width and leaf area are important for improving leaf yield potential and defining breeding strategies for genetic improvement of dry leaf yield (Bayat et al, 2014). In this investigation, no positive association was found between yield and leaf properties.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…G1, G3, G4, G9, G13, G16, G18, G21, G22 and G24) could be used for improving fresh and dry leaf yield traits in tobacco breeding program. The leaf properties including leaf length, leaf width and leaf area are important for improving leaf yield potential and defining breeding strategies for genetic improvement of dry leaf yield (Bayat et al, 2014). In this investigation, no positive association was found between yield and leaf properties.…”
Section: Discussionmentioning
confidence: 52%
“…2). According to Bayat et al, (2014), a significant positive correlation was observed between dry leaf yield and fresh weight of leaf and plant height.…”
Section: Vector View Of Biplotmentioning
confidence: 99%
“…Harvests were done at technical maturity and leaves were sun-cured. The plants were not topped as is common with most other tobacco types such as Virginia and burley (BAYAT et al, 2014).…”
Section: Cultural Practicesmentioning
confidence: 99%